Structure and discourse in the decolonial teaching of the Portuguese language: a discursive approach - Pereira Daróz, Elaine; Gama Dos Santos, Kauan Douglas (Revista Letras Raras, 2024)
We observed that a descriptive perspective still predominates in the teaching of the Portuguese language in Brazil, centered on the overvaluation of the standard norm. We understand that this approach enables the perpetuation of a hierarchy between the different ways of speaking in our country, producing implications for subjects' identity issues in their relationship with language and their history. The aim of this article is to highlight how literature, especially regionalist literature, can contribute to the teaching and learning of Portuguese from a decolonial perspective. To this end, we have drawn on the theoretical-analytical principles of Discourse Analysis from a materialist perspective, insofar as it provides us with greater support for a reconfiguration of language teaching practices, with historicity as the founding element. From this perspective, we present an activity carried out as part of the Literature for All project, as a possibility of working with a theory in practice, with a view to re-signifying subjects in society.